Fluid injection in Enhanced Geothermal Systems: a study on the detectability of self-potential effects and on their correlation with induced seismicity. (January 2017) - Troiano, A.; Di Giuseppe, M.G.; Monetti, A.; Patella, D.; Troise, C.; De Natale, G.
Abstract: We present a numerical modeling aimed at investigating nature and role of the self-potential (SP) anomalies induced by water injection in boreholes at the Soultz-sous-Forêts (SsF) hot dry rock enhanced geothermal field. The overpressure due to the fluid stimulation is considered as source of the streaming potential effects in rocks, responsible on their turn of the SP anomalies observed at the ground surface. The numerical simulations have been realized by a combined application of the TOUGH2 and Comsol Multiphysics codes, which had already been successfully used to predict Coulomb stress changes in rocks induced by a fluid injection cycle. Two synthetic cases are investigated. At first, a simulated injection cycle in a single borehole has been modeled, consisting in the reconstruction of the overpressure and SP temporal and spatial evolutions induced by the hydraulic stimulation of the rock. The main result is that the front of the SP anomaly follows the overpressure front, with the time delay between the two fronts decreasing at increasing distance from the well. The second case takes into consideration a real injection experiment performed in 2003 at SsF, which has allowed to examine the induced seismicity. The simulated SP response to this real injection cycle shows that the SP temporal evolution is essentially a post-seismic effect. The conclusion from the simulations is that SP measurements can be used to localize the main features of the fluid flow into the reservoir.